Students’ perceptions of English teachers’ emotional intelligence in shaping their speaking skills: A qualitative study - Dilasani, Refina; Sudiran; Hartono (English Education Department, Universitas Islam Indonesia, 2025)
Teachers’ emotional intelligence has become an important part in students’ learning outcomes and experiences especially in English as a Foreign Language (EFL) context. This study focuses on high school students’ perceptions of their teachers’ emotional intelligence and its impact on their speaking skills and classroom engagement. This is a case study. Eight third-grade students in different senior high schools who have known of their teachers’ personalities during the educational process were interviewed. The findings showed that teachers’ positive emotions can increase students’ self-confidence and motivate them to improve their English speaking skills. Conversely, when teachers expressed impatience or anger in front of the classroom, it could decrease students' learning engagement, as they experienced stress and fear about making sounds in the classroom. This study revealed that emotional intelligence is very important in creating a positive learning environment, making English classes much more effective, and helping students improve their speaking skills.